Impact of Skeletal Malocclusion on Quality of Life - Masjedi, Mashallah Khaneh; Araban, Marzieh; Neysi, Mokhtar Abidi (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
Introduction: nowadays, one of the remarkable issues in dentistry is jaw growth pattern and tooth and mouth conditions (oral conditions) on patients’ quality of life and daily activities. This study was done to evaluate skeletal malocclusion effect on the quality of life and oral health in Ahvaz. Methods: 80 people with skeletal malocclusion and 80 people with normal skeletal occlusion (control) participated in this cross-sectional study. Data collection tools included: demographic and oral health impact questionnaires. Results: there is not any significant difference between average quality of life of people with Cl III and Cl II skeletal (p=0.761), but there is a meaningful relation between Cl II skeletal and normal skeletal groups and also between Cl III skeletal and normal skeletal groups (p<0.001). Conclusion: according to social and moral issues importance in raising the quality of life score and because study results showed that these patients are not in good condition of that, considering different moral and social aspects of oral condition in presenting dentistry services are suggested to develop general quality of life